Basic College Mathematics (9th Edition)

Published by Pearson
ISBN 10: 0321825535
ISBN 13: 978-0-32182-553-7

Chapter 9 - Basic Algebra - 9.4 Order of Operations - 9.4 Exercises: 1

Answer

$(-6)^{2} -8 \div 2(-3) = 48$

Work Step by Step

1. Complete the exponent in $(-6)^{2}$ by multiplying $(-6 \times -6)$ 2. Do the division by dividing $(8)$ with $(2)$ 3. Complete the multiplication 4. Finally, subtract the values $= (-6)^{2} -8 \div 2(-3)$ $= ((-6) \times (-6)) - 8 \div 2 \times (-3)$ $= (36) - 8 \div 2 \times (-3)$ $= (36) - 4 \times (-3)$ $= 36 - (-12)$ $= 36 + 12$ $= 48$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.